Penggunaan Price Earning Ratio Dan Price To Book Value Sebagai Dasar Pengambilan Keputusan Investasi Saham (Studi Pada Perusahaan Sub Sektor Batubara Yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2020-2022) - St. Hasnia; Amiruddin Tawe; Nurman Nurman; Anwar Anwar; Muhammad Ichwan Musa (Lembaga Pengembangan Kinerja Dosen, 2023)
The aim of this research is to determine the application of the Price Earning Ratio and Price to Book Value as a basis for making stock investment decisions in coal sub-sector companies listed on the IDX for the 2020-2022 period. The population in this study are coal sub-sector companies listed on the IDX in 2020-2022. Sampling used a purposive sampling technique and eight company samples were obtained. Data collection techniques use documentation. Data analysis techniques use PER and PBV. The results of this research show that based on intrinsic value calculations using PER and compared with closing price, company shares that are undervalued include ADRO, BSSR, BYAN, GEMS, ITMG, MBAP, MYOH, and PTBA where the investment decision that can be taken is to buy shares or holding shares if already owned. Based on the intrinsic value calculation using PBV and compared with the closing price, company shares that are undervalued include ADRO, BYAN, GEMS, ITMG, MBAP, MYOH, and PTBA where the investment decision that can be taken is to buy shares or hold shares if they have owned, and one company, namely BSSR, is in an overvalued condition where the investment decision that can be taken is to sell shares.